Molecular characterization and expression analysis of the CCR9 gene from cobia (Rachycentron canadum) following bacterial and poly I:C challenge. Issue 1 (1st January 2019) - Su, Youlu; Deng, Yiqin; Cheng, Changhong; Ma, Hongling; Guo, Zhixun; Feng, Juan
ABSTRACT: Chemokine receptors play an important role in coordination of cell trafficking in many biological processes. In this study, a CC chemokine receptor 9 of cobia Rachycentron canadum ( RcCCR9 ) was identified. Analysis of the ORF (1119 bp) of RcCCR9 revealed a predicted protein of 41.87 kDa with typical seven transmembrane domain architecture. RcCCR9 shared several conserved structural features with homologs from mammals and other fish, and had a consistent relationship with phylogenetic trees and sequence identities. Reverse transcription quantitative PCR analysis showed ubiquitous RcCCR9 transcripts in healthy cobia, mainly in immune-related organs, with the highest levels in blood and lower levels in intestines and brain. After challenge with inactivated Vibrio harveyi or viral mimic poly I:C, RcCCR9 expression was up-regulated in head kidney and down-regulated in spleen. Compared with poly I:C, V. harveyi induced a stronger up/down-regulation of CCR9 mRNA levels in the central immune organs. RcCCR9 seems to be strongly involved in host defense against bacterial infection.